Liquid phase exfoliation of carbonate-intercalated layered double hydroxides - Coleman, Jonathan (My University, 2019)
Direct exfoliation of a carbonate layered double hydroxide (LDH) has been achieved by using a novel horn-probe sonic tip, avoiding the development of time-consuming anion-exchange reactions. The most suitable solvents were chosen based on the Hildebrand solubility parameters and the thickness of the exfoliated nanosheets confirmed unambiguously the successful delamination
PUBLISHED
Keywords: carbonate layered double hydroxide; carbonate layered double hydroxide